Mineralisasi Nitrogen Kompos Campuran Residu Kedelai Dan Jerami Padi Berbagai Komposisi - Anis Sholihah; Agus Sugianto; M. Taqiudin Alawy (Folium : Jurnal Ilmu Pertanian, 2021)
This study aims to determine the quality of the compost and the amount of nitrogenrelease resulting from mineralization from the compost mixture of soybean residuesand rice straw. The research was conducted in two stages; Stage 1. Making a compostmixture of soybean residue and rice straw with 5 mixed compositions, namely; D1 =100% soybean residue; D2 = 75% soybean residue + 25% rice straw; D3 = 50%soybean residue + 50% rice straw; D4 = 25% soybean residue + 75% rice straw; D5 =100% rice straw. Stage 2.The unwashed incubation experiment aims to determine theamount of nitrogen mineralization from the results of the compost mixture of stage 1 bymeasuring the amount of nitrogen released into the soil, the experiment uses acompletely randomized design (CRD) with the same mixed compost treatment withstage 1 plus 2 comparative treatments, namely control treatment and NPK treatment(D6). The results showed that the mixture of organic matter with different residualqualities of soybean and rice straw gave the same dynamics of N mineralization wherethe cumulative N mineral increased with the increase of soybean residue in the mixtureduring the incubation period (1,2,4 and 8 weeks). Treatment D1 (100% soybeanresidue) showed the highest rate of mineralization and the amount of N released(mineral N) of 0.0602 mg week -1 and 1225.39 mg kg-1, respectively.